Acceptance of multicultural society on the Hudud bill implementation in Malaysia / Azzah Nasiha, Jani Ayub Khan and Syaripah Ruzaini Syed Aris - Nasiha, Azzah; Ayub Khan, Jani; Syed Aris, Syaripah Ruzaini (Centre for Media and Information Warfare Studies, 2017)
Recently, the Hudud Bill implementation in Kelantan has generated tension among the multicultural society in Malaysia. A countless number of populace has given different points of view regarding on this matter. The Islamic law issue has continued to create a major gap between the ruling and opposition parties as they struggle to accept the Hudud Bill practice in Malaysia which was proposed by the Pan-Malaysian Islamic Party. Indeed, Malaysia is a developing Islamic country and mostly inhabited by the Malay race. However, the issue has also flourished among the Malaysian society as it has divided the legal system between the Muslim and non-Muslim in the Kelantan region. Thus, this research seeks to study the acceptance of multicultural society in Malaysia towards the implementation of the Hudud Bill. The main objectives of this research are to identify the acceptance factors that enlighten the multicultural society on the implementation of the Hudud Bill and provide recommendation related to the implementation of Hudud Bill to relevant parties that enhance awareness within the multicultural society. Therefore, the study will employ quantitative methods in order to reach the objectives of the research. The research is using survey methods and examinations were carried out within different groups in Kuching, Sarawak. 500 questionnaires had been distributed around the target area by the researcher. Consequently, through the findings it produced the outcomes that indicated on how the Hudud Bill implementation affects the acceptance factors within the multicultural society. The results of this research will become as an instruction to the any relevant parties in developing a future solution in regards to the acceptance of multicultural society in Malaysia, as well as a guideline for further research.